The Urgency of Spiritual Healing during the Coronavirus Outbreak - M. Kharis Majid; Winda Roini; Azmi Putri Ayu Wardani; Maulida Hasyyah Sabrina (Teosofia: Indonesian Journal of Islamic Mysticism, 2022)
Pandemic COVID-19 has led to a sharp decline in the economic aspect, educational activities considered less effective, and difficulty performing worship. As a result, people's anxiety has increased dramatically. This study aims to reveal the urgency of spiritual healing in the life of the community during the Pandemic COVID-19 to answer the challenges of how effective it is in tackling the crucial erosion of spirituality amid society. This article is library-based research, and the data were gathered using documentary approaches. With the descriptive analysis approach, using al-Ghazālī's idea of Ma'rifatullāh, this study found that Ma'rifatullāh, through self-recognition, will lead someone to a more peaceful and calmer situation. Its position as a centre of spiritual healing in Taṣawwuf teachings is very effective in overcoming the crisis experienced by the community during the pandemic. Thus, the anxiety and worldly concerns will transform into peace and tranquillity.Contribution: This article reveals that self-tranquillity and peace are sometimes not dealing with worldly affairs. Instead, it is about spiritual things. However, many tend to forget that the root of their tranquillity is found in the spiritual dimension.